2015
DOI: 10.1111/1750-3841.12984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of β‐Lactamase Producing Escherichia coli from Retail Meat in Turkey

Abstract: Extended spectrum β-lactamase (ESBL) and plasmid-mediated AmpC β-lactamase (pAmpC) producing Escherichia coli have been shown to be present in humans and animals representing a significant problem worldwide. This study aimed to search the presence of ESBL and/or AmpC-producing E. coli in retail meats (chicken and beef) in Turkey. A total of 88 β-lactamase-producing E. coli were isolated from chicken (n = 81/100) and beef meat (n = 7/100) samples and their susceptibility to several antimicrobials were tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
27
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 38 publications
11
27
3
Order By: Relevance
“…In order to assess the variation among ESBL‐EC isolates we conducted phlo‐typing method as well as PFGE. As consisting with the previous findings (Pehlivanlar Önen et al, ), phylo‐group B 2 , that has been identified as the pathogenic strain to humans, was identified only in few isolates from both samples, whereas the majority of isolates belonged to phylo‐group D, which was identified as the low virulent group (Clermont et al, ). Our results are in line with other studies that identified the low virulent groups commonly from foods of animal origins (Egea et al, ; Mo, Slettemeås, Berg, Norström, & Sunde, ; Tansawai, Sanguansermsri, Na‐udom, Walsh, & Niumsup, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In order to assess the variation among ESBL‐EC isolates we conducted phlo‐typing method as well as PFGE. As consisting with the previous findings (Pehlivanlar Önen et al, ), phylo‐group B 2 , that has been identified as the pathogenic strain to humans, was identified only in few isolates from both samples, whereas the majority of isolates belonged to phylo‐group D, which was identified as the low virulent group (Clermont et al, ). Our results are in line with other studies that identified the low virulent groups commonly from foods of animal origins (Egea et al, ; Mo, Slettemeås, Berg, Norström, & Sunde, ; Tansawai, Sanguansermsri, Na‐udom, Walsh, & Niumsup, ).…”
Section: Discussionsupporting
confidence: 85%
“…ESBL‐EC have been frequently isolated from the foods of animal origins such as chicken meat, fish and raw milk (Brahmi et al, ; Odenthal, Akineden, & Usleber, ; Pehlivanlar Önen, Aslantaş, Yılmaz, & Kürekci, ), which resulted in great attention to study the molecular epidemiology of ESBL‐EC strains for human illnesses during the last decade. Even though the exact source of ESBL‐EC strains for human infections has not been clearly understood yet, a series of experiments have presented convincing evidence implicating contaminated foods of animal origin as possible route of transmission to humans (Leverstein van Hall et al, ; Zurfluh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CTX-M-15 is also the most commonly reported enzyme type in E. coli isolates from human clinical samples [2, 13, 19]. Recent studies in Turkey shows presence of this enzyme among ESBL producing E. coli isolates in cattle and retail meat [3, 37]. To a lesser extent, CTX-M-3 and CTX-M-1, were detected in nine and three isolates alone, also eight and 12 isolates in combination with other β-lactamase genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among the CMY family, CMY-2 type is most frequently encountered around the world. In Turkey, CMY-2 producing E. coli has been reported in humans, cattle and retail meats [3, 37, 52]. …”
mentioning
confidence: 99%
“…In their study, the authors detected only OXA-10 and SHV-5 as ESBL enzymes together with TEM-1. Recently, Önen et al [22] reported higher contamination rate of chicken meat with ESBL producing E. coli, but low contamination rate for beef meat (7%) in Turkey. In contrast, Başaran Kahraman et al [23] , who investigated the presence of ESBL and AmpC β-lactamase producing E. coli from faecal samples of broiler and egg-type healthy chicken belonging to 43 flocks, reported prevalence of ESBL and AmpC producers as 7.8% and 3.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%